2019
DOI: 10.1017/s1355617719000821
|View full text |Cite
|
Sign up to set email alerts
|

Examining Gender Differences in Neurocognitive Functioning Across Adulthood

Abstract: Objective:Previous research has shown that women have an advantage on verbal episodic memory and processing speed tasks, while men show an advantage on spatial ability measures. Previous work has also found differences in cognition across age. The current study examines gender differences in neurocognitive functioning across adulthood, whether age moderates this effect, and whether these differences remain consistent with practice across multiple testing sessions.Method:Data from the Virginia Cognitive Aging P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 62 publications
2
13
1
Order By: Relevance
“…When examining measurement invariance between the two sexes, thus whether a cognitive profile would fit equally well to males and females, we again found an acceptable but not excellent model fit already in the configural model (composition of the components), with further significant decreases when it comes to mean and intercept invariances. While some fit values do not differ from previous results obtained by Siedlecki et al 22 , who interpreted a CFI value of 0.941 as being acceptable, they are low as compared to other studies investigating measurement invariance in cognitive or psychological profiles between, e.g. healthy adults and Alzheimer patients or using longitudinal models of sex differences over the whole adulthood 61 , 62 .…”
Section: Discussioncontrasting
confidence: 79%
See 2 more Smart Citations
“…When examining measurement invariance between the two sexes, thus whether a cognitive profile would fit equally well to males and females, we again found an acceptable but not excellent model fit already in the configural model (composition of the components), with further significant decreases when it comes to mean and intercept invariances. While some fit values do not differ from previous results obtained by Siedlecki et al 22 , who interpreted a CFI value of 0.941 as being acceptable, they are low as compared to other studies investigating measurement invariance in cognitive or psychological profiles between, e.g. healthy adults and Alzheimer patients or using longitudinal models of sex differences over the whole adulthood 61 , 62 .…”
Section: Discussioncontrasting
confidence: 79%
“…Averaged over the two sexes, cognitive performance decline is well established during the aging process 24 27 with a significant decline starting in the mid 50’s 24 , especially in the domains of executive functions, working memory and episodic memory. However, previous studies not only showed that sex-differences in cognitive performance persist until late adulthood 2 , 22 , 23 , they also reported unbalanced prevalence in neurodegenerative diseases that are accompanied by different cognitive impairments, i.e. males rather suffer from MCI and Parkinson’s disease, while females are more often affected by Alzheimer’s disease 28 , 29 .…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…As sex differences are present in both BMI 4 and cognitive abilities 6 across adulthood, associations between the two phenotypes must be considered by sex. How BMI reflects body fat may differ for men and women.…”
Section: Introductionmentioning
confidence: 99%
“…In the second series of models, the statistically significant ( p ≤ 0.05) sleep-wake disturbances variables from the first series of models were entered as independent variables. The covariates of age (Cansino, 2009), gender (Siedlecki et al, 2019), body mass index (Loprinzi & Frith, 2018), and health conditions (Edwards et al, 2018) were entered in the second regression models if they were significantly correlated with episodic memory at p < 0.05 (Tabachnick & Fidell, 2013).…”
Section: Methodsmentioning
confidence: 99%